FUZZY ASSIGNMENT PROBLEM USING OAM WITH HEXAGONAL FUZZY NUMBER - ALEXISSELVARAJ, H.; NARAYANAMOORTHY*, S.; MURUGESAN, V.; SANTHIYA, M. (International Journal of Mathematical Archive, 2018)
In this research paper, we used ones assignment method to find the fuzzy optional total cost of fuzzy assignment problem. Hence the robust ranking technique with hexogonal fuzzy number is presented, a numerical example is examined for the proposed method.